A Dual-Band High-Gain Subwavelength Cavity Antenna with Artificial Magnetic Conductor Metamaterial Microstructures - Guang Lu; Fabao Yan; Kaiyuan Zhang; Yunpeng Zhao; Lei Zhang; Ziqian Shang; Chao Diao; Xiachen Zhou (Micromachines, 2021)
This paper presents dual-band high-gain subwavelength cavity antennas with artificial magnetic conductor (AMC) metamaterial microstructures. We developed an AMC metamaterial plate that can be equivalent to mu-negative metamaterials (MNMs) at two frequencies using periodic microstructure unit cells. A cavity antenna was constructed using the dual-band AMC metamaterial plate as the covering layer and utilizing a feed patch antenna with slot loading as the radiation source. The antenna was fabricated with a printed circuit board (PCB) process and measured in an anechoic chamber. The |S11| of the antenna was −26.8 dB and −23.2 dB at 3.75 GHz and 5.66 GHz, respectively, and the realized gain was 15.2 dBi and 18.8 dBi at two resonant frequencies. The thickness of the cavity, a sub-wavelength thickness cavity, was 15 mm, less than one fifth of the long resonant wavelength and less than one third of the short resonant wavelength. This new antenna has the advantages of low profile, light weight, dual-frequency capability, high gain, and easy processing.